Impacts of the ACA Medicaid expansion on health behaviors: Evidence from household panel data. (15th November 2018) - Cotti, Chad; Nesson, Erik; Tefft, Nathan
Abstract: A motivation for increasing health insurance coverage is to improve health outcomes for impacted populations. However, health insurance coverage may alternatively increase risky health behaviors due to ex ante moral hazard, and past research on this issue has led to mixed conclusions. This paper uses a panel of household purchases to estimate the effects of the recent state‐level Medicaid expansions resulting from the Affordable Care Act (ACA) on consumption goods that present adverse health risks. We utilize within‐household variation to identify whether increases in Medicaid availability impacted household purchase patterns of alcohol, nicotine‐related, snack food, and carbonated beverage products. Overall, we find little evidence that the ACA Medicaid expansion led to ex ante moral hazard across any of these products, but we find compelling evidence that the Medicaid expansions reduced cigarette consumption and increased smoking cessation product use among the Medicaid‐eligible population.